Bankruptcy spillovers - Bernstein, Shai; Colonnelli, Emanuele; Giroud, Xavier; Iverson, Benjamin (Journal of Financial Economics, 2019)
How do different bankruptcy approaches affect the local economy? Using US Census microdata, we explore the spillover effects of reorganization and liquidation on geographically proximate firms. We exploit the random assignment of bankruptcy judges as a source of exogenous variation in the probability of liquidation. We find that employment declines substantially in the immediate neighborhood of the liquidated establishments, relative to reorganized establishments. The spillover effects are highly localized and concentrate in nontradable and service sectors, consistent with a reduction in local consumer traffic and a decline in knowledge spillovers between firms. The evidence highlights the externalities that bankruptcy design can impose on nonbankrupt firms.